Uwarunkowania modeli wartości młodego pokolenia. Na przykładzie uczniów klas VIII szkół podstawowych - Dyczewski, Błażej (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2022)
The article attempts to search for predictors of the value system of eighth graders of primary schools. The aim is to answer the question which predictors among those proposed (gender, degree of religious commitment, grade point average, family material situation, relationship with parents, playing games, relationship with the tutor, relationship with siblings) play the greatest importance in the choice of nine value models by adolescents. The research was carried out between 1.10.2018 and 12.01.2019 using a self-administered, auditorily completed online survey questionnaire (CAWI). The article refers to a sample of eighth-graders (N = 1986) that is representative in terms of province, gender and size of place of residence. The results show that gender is the strongest predictor, followed by grade point average, degree of religious commitment and family financial situation. Playing games and relationships with educator and siblings are less significant. Relationships with parents play the least important role.